Global Sourcing and Domestic Production Networks - Taiji Furusawa; Tomohiko Inui; Keiko Ito; Heiwai Tang (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper studies how firms' offshoring decisions shape a country's domestic production net- works. We develop a model in which heterogeneous firms source inputs from multiple industries located in different domestic regions and foreign countries. Input sourcing entails communication with suppliers, which is endogenously increasing in the differentiation of inputs. The model predicts that firms are less likely to source differentiated inputs, especially from distant domestic and foreign suppliers, due to costly communication. Triggered by foreign countries' export supply shocks, firms start offshoring inputs from foreign suppliers, which displace the less productive domestic suppliers in the same industry (the direct displacement effect). The resulting decline in marginal costs induces firms to start sourcing from the more productive and distant domestic suppliers within industries (the within-industry restructuring effect), but possibly also from nearby suppliers that produce inputs that are more differentiated than those supplied by existing suppliers (the industry composition effect). The net effect of offshoring on a firm's domestic production networks depends on the relative strength of the three effects, which we verify using data for 4.5 million buyer-seller links in Japan. Based on a firm-level instrument, we find that after offshoring, firms are less likely to drop suppliers on average, but more so for the larger ones. They tend to add nearby suppliers producing differentiated inputs. These results suggest that firms.offshoring may increase the spatial concentration of domestic production networks.
Keywords: D22; D85; F14; L10; L14; R12; 330; production networks; global sourcing; offshoring; face-to-face communication; industry agglomeration